Pelatihan Crowdfunding bagi UMKM Mitra Rumah BUMN Bandar Lampung - Redaputri, Appin Purisky; A, Aprinisa; Aprilinda, Yuthsi; Rizkyna, Shanaz; Santoso, Niki Agus (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
The importance of crowdfunding training for Micro, Small, and Medium Enterprises (MSMEs) in Bandar Lampung, with a focus on the challenges and opportunities faced. In the context of digitalization, community support is crucial to increase the visibility and credibility of MSMEs, which in turn can reduce the risks associated with crowdfunding. However, many MSMEs still do not understand the mechanism of crowdfunding. In addition, the lack of financial literacy among MSME owners is also an obstacle, so they cannot present attractive proposals to potential investors. Therefore, this article recommends the development of a tailored training program to improve the understanding and skills of MSMEs in using crowdfunding as an alternative funding, especially in challenging economic situations such as the post-COVID-19 pandemic. With the right approach, it is hoped that MSMEs can utilize crowdfunding for the growth and sustainability of their businesses.